Estudos de diversidade genética em estoques reprodutores de camarões Litopenaeus vannamei cultivados no Brasil - Freitas, Patrícia Domingues de (Universidade Federal de São Carlos, 2003)
The identification of genetic marks can provide information about the distribution of genetic variability in relation to populational size and parental generation, besides the discrimination of lines and/or individuals. Researches carried out in different shrimp species reared at captivity have demonstrated that a regular monitoring of the genetic variability levels of stocks, through identification of molecular markers, is essential to an adequate management orientation. In the present work, RAPD markers were used to evaluate the genetic diversity and to determine the divergence and identity relationships among different broodstocks of the marine shrimp Litopenaeus vannamei reared at Brazil. The DNA extraction was performed according to Sambrook et al. (1989) and PCR reactions were accomplished by using the kit Ready-To-Go RAPD Analysis Beads (Amersham Pharmacia Biotech). The percentage of polymorphic loci, allele frequencies, diversity indexes, and Nei´s genetic distance and identity were determined; and dendrograms of genetic similarity were built, by using the software POPGENE, version 1.31 (Yeh et al., 1999). The Jaccard´s genetic similarity coefficient, which ignores the absence of band as an indicator of similarity, was calculated by using the software NTSYS, version 2.0 (Rohlf, 1993). A total of 332 individuals from 19 broodstocks were analyzed, five of them belonging to a same inbred line. Sixty-four fragments were identified when a set of six primers was adopted to perform RAPD-PCR. The genetic diversity and similarity indexes demonstrated a reduced variability in stocks at initial domestication process. The analysis of genetic distance and identity evidenced that the reared stocks are closely related, lacking significant divergences. The values obtained in the inbreeding line revealed a progressive decreasing of genetic variation throughout the generations. The dendrogram demonstrated that as long as the generation increases, the genetic structure changes and becomes more and more distant from that observed in the first populations. According to analysis by non-linear regression, if this tendency is maintained, the levels of genetic variation can get close to zero before the stock reaches the 19th generation. The molecular data obtained in the present work reinforce the suggestion that the management nowadays carried out by Brazilian larviculture laboratories to compose and maintain broodstocks of L. vannamei, leads to a reduction of the levels of genetic diversity of captive populations. The development of genetically divergent lines and crossbreeding programs might contribute to the establishment of more adequate strategies.
Keywords: Genética; Variabilidade genética; Litopenaeus vannamei; RAPD; Camarão; Aqüicultura; CIENCIAS BIOLOGICAS::GENETICA